2023
DOI: 10.1088/2053-1591/acc92c
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro and in-vivo wound healing studies of Ag@TiO2NRs/GG hydrogel film for skin tissue regeneration

Abstract: One million cases of skin wounds, either closed or open wounds, necessitate wound treatments to improve the quality of life. In this study, gellan gum biopolymer (Ag@TiO2NRs/GG) hydrogel film with Ag loaded TiO2 nanorods was fabricated for wound healing dressing. The wound healing performance of Ag@TiO2WR/GG hydrogel was tested in vitro and in vivo to investigate its ability to regenerate skin tissue. FTIR, XRD, and SEM were used to examine the physical and chemical properties of prepared Ag@TiO2NRs/GG hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…224 In another study, gellan gum biopolymer hydrogel film with Ag-loaded TiO 2 nanorods (Ag@TiO 2 NRs/GG) based wound healing dressing was developed for evaluation of skin tissue regeneration. 225 The results of this study reported 100% wound healing using Ag@TiO 2 NRs/GG hydrogel as revealed through clear dermis, thicker epidermis, and subcutis layer after 14 days of treatment. Furthermore, MgO nanoparticles doped cellulose hydrogel were developed for pH triggered sustained release of doxorubicin and demonstrated efficient antibacterial and anti-cancer effects.…”
Section: Experimental Nps Incorporated Hydrogels In Delivery Of the A...mentioning
confidence: 64%
“…224 In another study, gellan gum biopolymer hydrogel film with Ag-loaded TiO 2 nanorods (Ag@TiO 2 NRs/GG) based wound healing dressing was developed for evaluation of skin tissue regeneration. 225 The results of this study reported 100% wound healing using Ag@TiO 2 NRs/GG hydrogel as revealed through clear dermis, thicker epidermis, and subcutis layer after 14 days of treatment. Furthermore, MgO nanoparticles doped cellulose hydrogel were developed for pH triggered sustained release of doxorubicin and demonstrated efficient antibacterial and anti-cancer effects.…”
Section: Experimental Nps Incorporated Hydrogels In Delivery Of the A...mentioning
confidence: 64%
“…The films are gas permeable and prevent bacteria from entering the wound site [ 241 , 242 ]. In light of this, a gellan gum (GG)-based hydrogel film (Ag@TiO 2 NRs/GG) containing Ag-loaded TiO 2 nanorods (TiO 2 NRs) was recently published [ 237 ] ( Figure 5 b). TiO 2 NRs, which have an elongated structure and are considered cutting-edge one-dimensional fillers, were utilized in the manufacturing process of hydrogel film.…”
Section: Promising Applications Of Nanomembranes and Nanoparticles In...mentioning
confidence: 99%